2020
DOI: 10.3390/s21010099
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Monitoring Based on Tracheal Sounds: Continuous Time-Frequency Processing of the Phonospirogram Combined with Phonocardiogram-Derived Respiration

Abstract: Patients with central respiratory paralysis can benefit from diaphragm pacing to restore respiratory function. However, it would be important to develop a continuous respiratory monitoring method to alert on apnea occurrence, in order to improve the efficiency and safety of the pacing system. In this study, we present a preliminary validation of an acoustic apnea detection method on healthy subjects data. Thirteen healthy participants performed one session of two 2-min recordings, including a voluntary respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…As shown in Figure 2 and Figure 4 , the amplitude of the LF-FCG and HF-FCG signals appeared to be modulated by respiration. Various studies on SCG [ 8 , 9 , 30 , 31 , 32 ] and heart sounds [ 33 , 34 , 35 , 36 ] have found consistent variation in the amplitude of signals during various phases of the respiratory cycle, and nearly no variability during apnea. These results are consistent with those obtained from this study.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 2 and Figure 4 , the amplitude of the LF-FCG and HF-FCG signals appeared to be modulated by respiration. Various studies on SCG [ 8 , 9 , 30 , 31 , 32 ] and heart sounds [ 33 , 34 , 35 , 36 ] have found consistent variation in the amplitude of signals during various phases of the respiratory cycle, and nearly no variability during apnea. These results are consistent with those obtained from this study.…”
Section: Discussionmentioning
confidence: 99%
“…The above clinical research was consistent with our study, which illustrated that the EPR combined with EDP therapy could increase the activity of the diaphragm in patients, thereby ensuring the oxygen supply. At the same time, this treatment also promotes the recruitment of and maintains the proportion of diaphragmatic fibres and slows down diaphragmatic atrophy [28].…”
Section: Discussionmentioning
confidence: 99%
“…Lu's team proposed a method of breathing monitoring based on tracheal sounds called cardiac sound-derived respiration (PDR). They collected sound signals, then postprocessed the recordings in both the time domain and frequency detection domains, and finally compared them with electrocardiograms to detect apnea [15]. Preeti Jagadev et al used infrared imaging equipment to detect respiration by observing the temperature changes of the chest, neck, mouth and nose during respiration and extracting dynamic thermal eigenvalues, but this method was greatly affected by ambient temperature [16].…”
Section: Introductionmentioning
confidence: 99%